A Case of Fetal Diagnosis of Noncompaction Cardiomyopathy and Coarctation of the Aorta - Katherine Jacobs; Lauren Giacobbe; Marijo Aguilera; Kirk Ramin; Shanthi Sivanandam (Thieme Medical Publishers, Inc., 2014)
Abstract Background Left ventricular noncompaction (LVNC) cardiomyopathy is a rare form of cardiomyopathy. It is difficult to diagnose prenatally and therefore not well described in the fetal population. There have been a few reports in the literature detailing isolated cases of fetal and neonatal LVNC cardiomyopathy. Case Report We present a case of LVNC cardiomyopathy and coarctation of the aorta detected prenatally at 29 + 6 weeks of gestation with survival in infancy. This is the first case report in the literature describing the fetal diagnosis of noncompaction cardiomyopathy and associated coarctation of the aorta; a rare combination. Conclusion  With a high index of suspicion, the antenatal diagnosis of noncompaction cardiomyopathy may improve neonatal morbidity and mortality.